Parchemos: arts, politics and communication at school - Soler Rubio, Ricardo Alfonso; Viasús Quintero, Guillermo Alfonso (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
This article presents the results of the research project called “Parchemos: creando paz desde la comunicación en la escuela y en el barrio” framed in the fellowship of Action Research in Democratic Culture Guillermo Hoyos Vásquez, on its 2015 version. The Project aimed to strengthen the civic practices at school context of the ninth grade from the District Educative Institution Eduardo Umaña Luna, in search of peace construction and democratic culture using communication as a political stake, improving these processes from musical and visual arts.